2019
DOI: 10.1186/s12885-019-5354-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk and consequences of chemotherapy-induced thrombocytopenia in US clinical practice

Abstract: Background Chemotherapy-induced thrombocytopenia (CIT) is a potentially serious complication that can lead to chemotherapy dose delays, dose reductions, or discontinuation, and increases the risk of serious bleeding events. The objectives of this study were to characterize the incidence, clinical consequences, and economic costs of CIT in current US clinical practice. Methods A retrospective cohort design and data from two US private healthcare claims repositories (01/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 13 publications
(18 reference statements)
4
91
2
1
Order By: Relevance
“…10 In a recently published retrospective study based on data obtained from two U.S. private health care claims repositories (temporal range: January 2010 to December 2016), the incidence of CIT among 215,508 patients receiving chemotherapy was 9.7% (95% confidence interval [CI]: 9.6-9.8), ranging from 6.1% (95% CI: 5.9-6.3%) for treatments containing cyclophosphamide to 13.5% (95% CI: 12.7-14.3%) for those containing gemcitabine. 9 The frequency of CIT has, however, partially declined over the years. In a retrospective analysis performed in 1984 including 501 patients affected by gynecologic cancer treated with chemotherapy, CIT had developed in 36.3% of patients, 11 whereas a study conducted 15 years later reported that CIT occurred in 14.8% of patients.…”
Section: Drug-induced Thrombocytopenia Through Bone Marrow Suppressiomentioning
confidence: 99%
“…10 In a recently published retrospective study based on data obtained from two U.S. private health care claims repositories (temporal range: January 2010 to December 2016), the incidence of CIT among 215,508 patients receiving chemotherapy was 9.7% (95% confidence interval [CI]: 9.6-9.8), ranging from 6.1% (95% CI: 5.9-6.3%) for treatments containing cyclophosphamide to 13.5% (95% CI: 12.7-14.3%) for those containing gemcitabine. 9 The frequency of CIT has, however, partially declined over the years. In a retrospective analysis performed in 1984 including 501 patients affected by gynecologic cancer treated with chemotherapy, CIT had developed in 36.3% of patients, 11 whereas a study conducted 15 years later reported that CIT occurred in 14.8% of patients.…”
Section: Drug-induced Thrombocytopenia Through Bone Marrow Suppressiomentioning
confidence: 99%
“…Thrombocytopenia, an abnormally low blood platelet count, is a common side effect of myelosuppressive chemotherapy 1‐3 . Prior studies estimated that approximately 10% to 38% of patients with a solid tumor and 40% to 68% of patients with a hematologic malignancy experience thrombocytopenia 3‐7 . The incidence and prevalence of chemotherapy‐induced thrombocytopenia (CIT) vary greatly by type of cancer and chemotherapy regimen, for example, from 16% in head and neck cancer to 68% in hematologic cancers, and from 8% in taxane‐based regimens to 37% in gemcitabine‐based regimens and 82% in carboplatin monotherapy 2,3,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies estimated that approximately 10% to 38% of patients with a solid tumor and 40% to 68% of patients with a hematologic malignancy experience thrombocytopenia 3‐7 . The incidence and prevalence of chemotherapy‐induced thrombocytopenia (CIT) vary greatly by type of cancer and chemotherapy regimen, for example, from 16% in head and neck cancer to 68% in hematologic cancers, and from 8% in taxane‐based regimens to 37% in gemcitabine‐based regimens and 82% in carboplatin monotherapy 2,3,7,8 . Gemcitabine‐based and platinum‐based regimens have consistently been associated with the highest risk of thrombocytopenia 1‐3 .…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial regimens of ATRi with chemotherapy could also benefit from combination with subtherapeutic doses of DNA-damaging agents. Chemotherapeutics such as antimetabolites, crosslinking agents, or topoisomerase inhibitors (e.g., gemcitabine, cisplatin, or topotecan, respectively) can also cause myelosuppression by themselves [ 161 , 162 , 163 ]; thus, dose reduction might prevent their potential toxic events.…”
Section: Lessons Learned From the Clinical Trialsmentioning
confidence: 99%